Behavioural and neurochemical effects after repeated administration of N‐ethylpentylone (ephylone) in mice. Issue 2 (8th December 2021) - Espinosa‐Velasco, María; Reguilón, Marina D.; Bellot, Marina; Nadal‐Gratacós, Núria; Berzosa, Xavier; Puigseslloses, Pol; Gómez‐Canela, Cristian; Rodríguez‐Arias, Marta; Pubill, David; Camarasa, Jordi; Escubedo, Elena; López‐Arnau, Raúl
Abstract: N‐ethyl‐pentylone (NEP), also known as 'ephylone' and N‐ethylnorpentylone, has been identified as one of the most recent novel psychostimulants to emerge into the illicit drug market and it has been associated with some intoxications and even fatalities. However, little is known about the consequences of its repeated consumption as well as the role of the monoaminergic system in such consequences. Thus, the aim of our study was to investigate the neurochemical profile and the behavioural effects after both acute and repeated NEP exposure. Male OF1 mice were acutely (1, 3, 10 mg/kg, i.p.) or repeatedly (1, 3, 10 mg/kg, i.p., 5 days, twice/day) exposed to NEP, and anxiety‐like behaviour, aggressiveness, social interaction, depressive‐like symptoms, body temperature, changes in monoaminergic enzymes and neurotransmitters levels as well as ΔFosB in striatum and prefrontal cortex (PFC) from post‐mortem tissue were analysed short after drug‐exposure or during drug‐withdrawal. Acute administration of NEP induced anxiolytic effects but also an aggressive behaviour and social exploration deficits in mice, which persist during NEP‐withdrawal. Moreover, NEP induced hyperthermia as well as depressive‐like symptoms after repeated administrations that may be related to the decrease in serotonin and noradrenaline levels observed in striatum and PFC. Finally, the long‐term increase in ΔFosB levels in striatum after NEP chronic exposure points to a high risk of dependence. Altogether indicates that NEP consumption induces different neurological and neuropsychiatric disorders accompanied by changes in the monoaminergic system, posing a threat to public health. Abstract : N‐ethyl‐pentylone (NEP) is a novel psychostimulant associated with several intoxications and fatalities. This study revealed behavioural and neurochemical effects induced by repeated administration of NEP in mice. Animals showed hyperthermia and decreased body weight gain during NEP‐treatment. Regarding withdrawal, NEP induced hyperlocomotion, depressive‐like symptoms and deficits in social interaction, accompanied by a decrease of serotonin and noradrenaline levels, as well as a dopamine imbalance, in striatum and prefrontal cortex. Moreover, long‐lasting increases of ΔFosB in striatum points to a high risk of dependence. In summary, repeated consumption of NEP induces neurological and neuropsychiatric disorders involving the monoaminergic system, posing a public health threat.